Pengembangan Media Pembelajaran Digital Berbantuan Quizwhizzer pada Topik Peredaran Darah Manusia di Kelas V SD Negeri 1 Sambijajar - Winda Fatmasari; Leny Suryaning Astutik (Jurnal Simki Postgraduate, 2024)
This research aims to develop, test the validity, and test the practicality of assisted digital media quizwhizzer on the topic of human blood circulation. This research uses the ADDIE development model which consists of analysis (Anaylsis), planning (Design), development (Development), Implementation (Implementation), and evaluation (Evaluation). The data collection technique was carried out by testing the validity of the media, materials, learning and distributing questionnaires. The instruments used in this research used media expert validation sheets, material expert validation, learning expert validation, teacher and student questionnaire sheets. The results of the average media validity are 86.5% in the "very valid" category. The average validity of material experts is 85.5%, included in the "very valid" category. The percentage of validity of media use for learning experts is 91% in the "very valid" category. Based on the results of the questionnaire, class V students at SD Negeri 1 Sambijajar obtained a percentage of 91% so they were declared "very practical". The results of the teacher questionnaire obtained 92.5% in the "very practical" category. So it can be concluded that digital learning media is assisted quizwhizzer on the topic of human blood circulation is declared valid and practical for use as a learning medium.